2017
DOI: 10.1177/1352458517734070
|View full text |Cite
|
Sign up to set email alerts
|

A population-based prospective study of optic neuritis

Abstract: The prospective incidence of ON was estimated. MRI enabled a diagnosis of MS in a subgroup of patients. Antibody-mediated ON with specificity for MOG was detected in 4% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 35 publications
3
69
0
1
Order By: Relevance
“…13 All participants had a clinical diagnosis of ON based on the criteria described by the Optic Neuritis Study Group. 13,15 OCT raised suspicion of central serous chorioretinopathy (CSCR) in one 39-year-old male patient 10 days after initial presentation. However, a de novo diagnosis of MS or NMOSD resulting from the qualifying ON event was explicitly allowed.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 All participants had a clinical diagnosis of ON based on the criteria described by the Optic Neuritis Study Group. 13,15 OCT raised suspicion of central serous chorioretinopathy (CSCR) in one 39-year-old male patient 10 days after initial presentation. However, a de novo diagnosis of MS or NMOSD resulting from the qualifying ON event was explicitly allowed.…”
Section: Patientsmentioning
confidence: 99%
“…13 Here, we report structural damage caused by ON, as quantified by OCT, from this population-based study. 13 Here, we report structural damage caused by ON, as quantified by OCT, from this population-based study.…”
Section: Introductionmentioning
confidence: 98%
“…The present study is nicely in line with another recent Danish population‐based prospective study, in which 51 patients with acute ON were identified during a 2‐year period in the Region of Southern Denmark (population: almost 1 million citizens) (Soelberg et al., 2017). Therefore, with the identification of 49 patients with acute ON in the current study, the procedure for referral of patients with ON can be considered to have been nearly complete.…”
Section: Discussionmentioning
confidence: 99%
“…The two Danish studies are also comparable when it comes to gender and age distribution. Furthermore, a similar number of patients were diagnosed with MS during the study period: 18 in the present study vs. 20 in the other study (Soelberg et al., 2017). In addition, no patients were seropositive for anti‐aquaporin‐4 antibodies, but both studies identified antibodies to myelin oligodendrocyte glycoprotein (MOG) in one patient with recurrent/bilateral ON (RON/BON) (Soelberg et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation